Hostile heartland: Racism, repression, and resistance in the Midwest - Campney, Brent M. S. (University of Illinois Press, 2019)
"We forget that racist violence permeated the lower Midwest from the pre-Civil War period until the 1930s. From Kansas to Ohio, whites orchestrated extraordinary events like lynchings and riots while engaged in a spectrum of brutal acts made all the more horrific by being routine. Also forgotten is the fact African Americans forcefully responded to these assertions of white supremacy through armed resistance, the creation of press outlets and civil rights organizations, and courageous individual activism. Drawing on cutting-edge methodology and a wealth of documentary evidence, Brent M.S. Campney analyzes the institutionalized white efforts to assert and maintain dominance over African Americans. Though rooted in the past, white violence evolved into a fundamentally modern phenomenon, driven by technologies such as newspapers, photographs, automobiles, and telephones. Other surprising insights challenge our assumptions about sundown towns, who was targeted by whites, law enforcement's role in facilitating and perpetrating violence, and the details of African American resistance."--Publisher's description.
Keywords: 1800-1899; 1900-1999; activisme; amériques; approches et analyses; cours; esclavagisme; his4443; histoire et politique; premier cycle; périodes historiques; racisme; régions géographiques; résistance; systèmes d'oppressions; thématiques; violence coloniale; violences; violences raciales; états-unis; états-unis (sud)

Fingersmith - Waters, Sarah (McClelland & Stewart, 2019)
Sue Trinder est une orpheline, laissée enfant aux soins de Mme Sucksby, une « petite agricultrice », qui l'a élevée avec une tendresse inhabituelle, comme si Sue était la sienne. La maison de Mme Sucksby, avec ses bébés difficiles calmés avec des doses de gin, accueille également une famille de petits voleurs de passage – des doigteurs – pour qui cette maison située au cœur d'un bidonville londonien est le foyer. Un jour, le voleur le plus aimé de tous arrive : Gentleman, un escroc élégant, qui apporte avec lui une proposition alléchante pour Sue : si elle remporte le poste de femme de chambre de Maud Lilly, une femme naïve, et aide Gentleman dans sa séduction. , alors ils partageront tous le vaste héritage de Maud. Une fois l'héritage obtenu, Maud sera éliminée, passée pour folle et obligée de vivre le reste de ses jours dans un asile d'aliénés. Avec le rêve de récompenser la gentillesse de sa famille adoptive, Sue accepte le plan. Une fois à l'intérieur, cependant, Sue commence à avoir pitié de sa cible impuissante et à prendre soin de Maud Lilly de manière inattendue... Mais rien ni personne n'est comme il semble dans ce roman de Dickens de frissons et de retournements.
Keywords: 1800-1899; care; europe; histoire et politique; périodes historiques; ressource en ligne; roman; royaume-uni; régions géographiques; thématiques; violences